2019
DOI: 10.1002/mgg3.921
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles and bioinformatics analysis of insulin‐like growth factor‐1 promotion of osteogenic differentiation

Abstract: Background Insulin‐like growth factor‐1 (IGF‐1) promotes osteoblast differentiation and mineralization. The objective of this study was to investigate the effects of IGF‐1 on proliferation, mineralization, alkaline phosphatase (ALP) synthesis, and gene expression of osteoblast differentiation in MC3T3‐E1 osteoblasts cells, and to explore gene expression profiling differential genes. Methods MC3T3‐E1 osteoblasts cells were cultured in medium with or without IGF‐1. The ALP assay was employed to determine the ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…IGF-1 recruits progenitor cells of the osteoblastic lineage 215 and promotes osteoblast differentiation and matrix mineralization by upregulating the osteogenesis‐related genes DMP1, PHEX, SOST, BMP2, RUNX2, OPN, and OCN. 216 Moreover, IGF-1 released from the bone matrix during bone resorption establishes an osteogenic microenvironment by activating mechanistic target of rapamycin (mTOR) signaling, 217 which is critical for cellular energy metabolism and cell migration. 218 Recent studies have confirmed that IGF-1-dependent activation of mTOR induces human dental pulp stem cell (DPSC) differentiation toward an osteoblastic phenotype.…”
Section: Osteoclastsmentioning
confidence: 99%
“…IGF-1 recruits progenitor cells of the osteoblastic lineage 215 and promotes osteoblast differentiation and matrix mineralization by upregulating the osteogenesis‐related genes DMP1, PHEX, SOST, BMP2, RUNX2, OPN, and OCN. 216 Moreover, IGF-1 released from the bone matrix during bone resorption establishes an osteogenic microenvironment by activating mechanistic target of rapamycin (mTOR) signaling, 217 which is critical for cellular energy metabolism and cell migration. 218 Recent studies have confirmed that IGF-1-dependent activation of mTOR induces human dental pulp stem cell (DPSC) differentiation toward an osteoblastic phenotype.…”
Section: Osteoclastsmentioning
confidence: 99%
“…IGF1 is a key protein in bone formation and plays an important role in the regulation of bone conversion and osteogenic growth ( 68 70 ). Yuan et al found that IGF1 promoted the differentiation of osteoblasts ( 71 ). Furthermore, Xue et al found that IGF1 promoted osteogenic differentiation of rat bone marrow mesenchymal stem cells by increasing TAZ expression ( 72 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, several studies used transcriptional profiling to address osteoblast differentiation. Some focus on gene expression profile of osteoporotic phenotype mice [41], and others used transcriptional analysis to investigate gene expression differences in osteoblast differentiation of MC3T3-E1 cells [42,43]. In this study, after we identified several common pathways and connected DEGs with potential biological pathways by transcriptome analysis, we found that EYG had an effect on several bone formation related pathways, such as TNF signaling pathway, complement and coagulation cascades, protein digestion and absorption, ECM-receptor interaction and focal adhesion.…”
mentioning
confidence: 99%